ANALYSIS OF THE RELATIONSHIP IN LEARNING INTEREST TO LEARNING OUTCOMES STATIC FLUID MATERIAL IN SENIOR HIGH SCHOOL - Oktavia, Sri Wina; Septiani, Neni; Sinaga, Feliza; Qoidah, Nikma Nur (LPPM Universitas Jambi, 2023)
This study uses a quantitative method using a questionnaire instrument distributed online which aims to analyze the relationship between learning interest and learning outcomes at SMA Negeri 4 Sungai Penuh academic year 2020/2021. The subjects in this study were students of class XI MIPA SMA Negeri 4 Sungai Penuh 72 people. Analysis of quantitative research using the SPSS program to test assumptions (normality and linearity) and making hypotheses through the correlation test obtained a person correlation value of 0.022 <0.05, so it is stated that Ho is rejected or there is a relationship between interest in learning and student learning outcomes physics in SMA Negeri 4 Sungai Penuh.